(untitled) (Acta Scientiarum. Agronomy, 2021)
Yacon is a perennial herbaceous plant that naturally occurs in South America at altitudes ranging from 2,000 m to 3,100 m above sea level. The yacon culture has recently grown in popularity as it has high productive potential in mild climates and multiple benefits to human health. This study aimed to determine the lower and upper base temperatures, cycle duration, and thermal constant for the yacon culture, based on phenological data from field experiments that were carried out during three growing seasons (fall, winter, and spring) in 2013. The experiments were conducted in the municipality of Ibatiba in the state of Espírito Santo, Brazil, in a randomized block design with four replicates. The lower base temperature was determined using methods of the lowest standard deviation in days and degree-days, relative development, and variation coefficient in degree-days for two subperiods: emergence to maturation, and onset of tuberization to maturation. The upper base temperature was determined by the standard deviation and coefficient of variation methods, both in degrees-days. The relationship between meteorological elements and the onset of tuberization was also investigated. The lower base temperature values determined for yacon were 12.5ºC in the two subperiods studied with a base temperature above 34.0ºC. The productivity of these tuberous roots was higher in the fall because of the longer cycle, lower temperature, and lower photoperiod. In turn, a higher thermal sum was needed to initiate tuberization with the delay of planting.